Implementation of Non-Invasive Detection of Cholesterol Levels, Hypertension Using Android-Based BPW34 and MPX5050GP Sensors - Junus, Mochammad; Rachmad Saptono; Nugroho Suharto; Daffa Afrizal Wijaya (Jurnal Informatika Polinema, 2025)
High cholesterol levels and blood pressure are the main indications of body health which can cause heart attacks and strokes. Cholesterol deposits in the blood vessels can cause narrowing which results in hypertension and disorders of the components of the cardiovascular system. In accordance with the function of the cardiovascular system which is responsible for sending blood to various parts of the body, it is necessary to detect cholesterol levels and hypertension as early as possible in order to prevent heart attacks and strokes. The aim of this research is to measure cholesterol and hypertension levels using the BPW34 and MPX5050GP sensors and the addition of the GY-MAX30100 sensor to detect heart rate and oxygen saturation. The three sensors were combined as an experimental analysis test for a prototype medical tool for measuring blood cholesterol levels and hypertension in real-time, non-invasively (does not injure skin tissue). In this research, an application system was created in the form of a dashboard of test results for each sensor, which then sent the medical test data results to the user's smartphone to determine estimated values for cholesterol and hypertension levels for the purpose of initial medical examination.In this research, an application system was created in the form of a dashboard of test results for each sensor, which then sent the medical test data results to the user's smartphone to determine estimated values for cholesterol and hypertension levels for the purpose of initial medical examination. The results of the research show that the prototype created compared to standard medical measuring instruments, has the ability to measure cholesterol levels and blood pressure with an accuracy of 0.675% on the BPW34 sensor and 3.9% on the MPX5050GP sensor and 1.475% accuracy on the GY-MAX30100 sensor. heart rate and 1.305% for oxygen saturation. The measurement data can be connected successfully into an android application enabling remote and live monitoring. This system supports personal health management by enabling people to monitor their health conditions independently and in real time.